The impacts of site factors towards building morphology in Kuala Lumpur / Nurul Amila Zulkepli and Yuhainis Abdul Talib - Zulkepli, Nurul Amila; Abdul Talib, Yuhainis (2023)
Site factors can give impacts on the building morphology and cost may be overrun. The presence of slopes, uneven terrain, and varying soil conditions can affect the stability of the building and the cost of implementing building construction increases depends on the site location. The objective of this research is to identify the impacts of site factors towards building morphology in Kuala Lumpur. A quantitative approach is used in this research and the data collected by using questionnaires survey. The findings reveal that there are three most significant impact on site factors are (i) transportation costs, (ii) type of foundation and (iii) site location. While the three least significant impact on site factors are (i) the presence of endangered trees, (ii) congested site, and (iii) occurrence of natural disaster. Therefore, these findings are important in determining building morphology, as well as for the designer to comprehend the effect on building morphology towards site factors.